Quantum tunneling of magnetization in ultrasmall half-metallic V3O4 quantum dots : displaying quantum superparamagnetic state - Xiao, Chong (2013)
Quantum tunneling of magnetization (QTMs), stemming from their importance for understanding materials with unconventional properties, has continued to attract widespread theoretical and experimental attention. However, the observation of QTMs in the most promising candidates of molecular magnets and few iron-based compounds is limited to very low temperature. Herein, we first highlight a simple system, ultrasmall half-metallic V3O4 quantum dots, as a promising candidate for the investigation of QTMs at high temperature. The quantum superparamagnetic state (QSP) as a high temperature signature of QTMs is observed at 16 K, which is beyond absolute zero temperature and much higher than that of conventional iron-based compounds due to the stronger spin-orbital coupling of V3+ ions bringing high anisotropy energy. It is undoubtedly that this ultrasmall quantum dots, V3O4, offers not only a promising candidate for theoretical understanding of QTMs but also a very exciting possibility for computers using mesoscopic magnets.